Invention and devotion in Giovanni Bellini's Uffizi Lamentation - Whistler, C (IRSA Publishing House, 2020)
This unusual work by Giovanni Bellini has been viewed variously in the scholarly literature as an unfinished painting, as a simile or model for the workshop to follow, or as an autonomous work of art. This paper explores the iconography in particular, proposing that Bellini’s treatment of the subject would have been indecorous in a fully-coloured painting for public viewing. Instead, it argues that Bellini probably made this for more restricted elite viewing, both as a devotional image and as a representation that afforded appreciation of aspects of his art. In creating a monochrome image in a compelling close-up form, Bellini incorporated allusions to relief sculpture. However, the particular graphic technique of the Lamentation evokes contemporary large-scale, virtuoso engravings, a context that also explains its early categorization as a work in ‘chiaro scuro’.